A Subject in Allegorical Clothing: The Case of ‘el maldiciente Clodio’ in Los trabajos de Persiles y Sigismunda - McCallister, Timothy A. (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This article considers the relationship between allegorical personification and literary subjectivity in Miguel de Cervantes’s Los trabajos de Persiles y Sigismunda (1617). Although previous scholarship has recognized the allegorical qualities of the character Clodio, a slanderer par excellence, these qualities have been seen as incompatible with his marked inner life. I begin by clarifying the understanding of speech vices in seventeenth-century Spain as a single vice measured by speech’s harmful effect. I then draw from philosophical and psychological studies on self-knowledge to argue that Clodio’s subjectivity is a function of his allegorical nature. His status as a personification of the speech vices gives rise to the introspection and agency that characterize him.